Modernizing Universities Through Quality Management And Innovative Pedagogical Technologies: Pathways To International Ranking Competitiveness (Journal of Pedagogical Inventions and Practices, 2026)
International ranking competitiveness is increasingly understood as a long-term outcome of how a university manages quality and renews its pedagogical practice rather than as a short-term effect of indicator optimisation. This article reports an experimental study designed to test the pedagogical effectiveness of integrating quality management mechanisms with innovative pedagogical technologies as a pathway to international ranking competitiveness. Drawing on the theoretical framework of internal quality assurance, quality culture and constructive alignment, the intervention combined programme-level key performance indicators, structured feedback cycles, problem-based and project-based learning, the flipped classroom and digital learning analytics within a coherent pedagogical model. A pre-test/post-test design with experimental (n = 246) and control (n = 243) groups was used. Group differences in mean competency were analysed with Welch’s independent samples t-test (robust to unequal variances) accompanied by Cohen’s d effect size with 95 per cent confidence intervals, while the distribution of competency levels was examined with a chi-square test of independence and Cramer’s V. After the intervention, the average competency score of the experimental group rose from 3.73 to 4.20, while the control group remained at 3.68. The mean difference of 0.52 was statistically significant, t(435.8) = 8.89, p < 0.001, 95% CI [0.41, 0.63], with a large effect size of Cohen’s d = 0.81, 95% CI [0.62, 0.99]. The chi-square test confirmed a highly significant redistribution of competency levels, χ²(2) = 118.10, p < 0.001, Cramer’s V = 0.49. Overall, the experimental group outperformed the control group by 11.5 per cent. The results provide empirical support for the proposition that the integration of quality management and innovative pedagogical technologies is a pedagogically grounded route to ranking-relevant institutional development